Teaching English by Using Audio-Visual Media - Sabila, Fitri; Krismawanti Modjanggo, Vivin (Sintuwu Maroso Journal of English Teaching, 2023)
This research aims to find out the use of audio-visual media in teaching English at SMP Negeri 2 Poso. This research is conducted at SMP Negeri 2 Poso. The research design is a qualitative research design using the case study method. The data are obtained from observations which are carried out two times in class VIII, interviewthe school principal, teacher, and three students, and documentation. The findings of this research show the teacher process in using audio-visual media in teaching English, but the process has not been implemented as expected as the theory suggested. The process consists of three steps. First, preparation or how the teacher prepares learning materials, learning tools, and prepares students. Second, implementation or application of audio-visual media to students, and the last is follow-up, in this process which the teacher carried out discussion and evaluation activities to students from audio-visual and learning materials.